Gêmeos assassinos & Duplos espelhos: Hannibal Lecter e Will Graham nos livros de Thomas Harris e na série televisiva de Bryan Fuller - Sell, Thaine Fernanda (2023)
This work is an analysis of the literary work Red Dragon by Thomas Harris, and its adaptation for the television series Hannibal by Bryan Fuller. For that, the double theory was used as theoretical support, from which the analysis of the characters Will Graham and Hannibal Lecter, central in this work, was carried out. In order to carry out the analysis, the aforementioned works were read, and a bibliographic review of the double theory was made. Therefore, the most appropriate passages for the purpose of the work were selected. This reference is constituted mainly by Otto Rank and Freud. With the central objective of analyzing how the double theory can serve as an answer to the various questions presented and developed by Bryan Fuller in his adaptation of the work of Thomas Harris, several passages were found in which this occurs in the television series. It is possible to perceive that the double is a possible answer because in many scenes the contrast between the characters is evidenced and its gradual approach, as well as the process of becoming similar, in addition to other aspects intrinsic to the double presented in the work. Will and Hannibal assume, in many moments, the image of each other, making it not clear, in some moments, their real identity.